Funding and sustainability in archives: a metasynthesis - Guardado da Silva, Carlos; Ascensão de Macedo, L. S. (Revista General de Información y Documentación, 2025)
The financial management of archives is essential to guarantee their continuity and access to information in the long term. This study explores how public and private policies affect the sustainability of these institutions, highlighting how the funding of these services is essential for the pursuit of their mission. A systematic review of the qualitative literature on the funding and sustainability of archives is carried out, identifying gaps and emerging trends. Preliminary results point to a scarcity of studies. Strategies include diversification of sources, innovative fundraising and partnerships. While museums have made significant progress in this area, archives face challenges such as a lack of financial transparency and the absence of comprehensive data, making international comparisons difficult. Public funding is crucial, but revenue diversification is necessary to ensure sustainability. In summary, archives need to adopt an entrepreneurial stance and be open to new opportunities to ensure their financial sustainability; futher research on these issues is also needed.
Keywords: Fundraising; archives; financing; financial transparency; sustainability